3D printing in medicine: current applications and future directions - Sun, Zhonghua (AME Publishing Company, 2018)
Technical developments in medical imaging techniques have led to significant improvements in the diagnostic performance of less-invasive imaging modalities such as computed tomography (CT), magnetic resonance imaging (MRI), nuclear medicine and ultrasound. Quantitative analysis of these imaging modalities allows for detection and diagnosis of various diseases with high accuracy (1-10). Despite promising results available in the literature, traditional two-dimensional (2D) and three-dimensional (3D) visualization tools are still limited to a 2D screen, which affect realistic visualization of anatomical structures and pathologies of 3D datasets, and this is particularly apparent when dealing with complex pathologies. This has created potential opportunities for the use of 3D printing technique in medical applications.